(untitled) (Biocenosis, 2023)
The botanical exploration that has been carried out in Costa Rica has been intense. However, knowledge about the total species richness of the country’s flora is far from complete. In this paper I present an account, based on a bibliographic review, of the new tree species that were discovered in Costa Rica between 2000 and 2022. This to succinctly expose the advances that have been made in terms of tree diversity in this country so far in the 21st century. The sources were located through the search engines of the DOAJ, JSTOR, SciELO, SpringerLink and Web of Science databases. Also, The Cutting Edge bulletin was reviewed. In total, 115 sources were found in which 191 new tree species of 81 genera and 39 families of angiosperms were described. Discoveries of species occurred during all years of the period analyzed, and they were distributed throughout the country’s territory, including Cocos Island. Based on the information collected, it can be affirmed that the taxonomic work carried out in Costa Rica has been constant and that knowledge about the number of tree species present in the country has been increasing year after year.